1991
DOI: 10.1111/j.1365-2818.1991.tb03156.x
|View full text |Cite
|
Sign up to set email alerts
|

A model for cryosectioning based on the morphology of vitrified ultrathin sections

Abstract: SUMMARY Electron microscopy of vitrified ultrathin sections allows cell ultrastructure to be studied in the hydrated state. Sectioning of the frozen material is, however, a limiting step, since the cutting forces cause severe mechanical deformation. In order to address this problem, we have investigated the surface of cryosections. It is shown that cryosections have two fundamentally different surfaces. One surface is rough, deformed by cutting‐induced deformation lines which are orientated perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…There are accumulations of crevasses on the large top KM and some top KM seem to be imprinted in the crevasses (white ellipses in A and B). This fact is in line with the observation of Richter et al (1991) that crevasses are on the top-side of the section.…”
Section: Cut-rotate-cut Experimentssupporting
confidence: 87%
See 1 more Smart Citation
“…There are accumulations of crevasses on the large top KM and some top KM seem to be imprinted in the crevasses (white ellipses in A and B). This fact is in line with the observation of Richter et al (1991) that crevasses are on the top-side of the section.…”
Section: Cut-rotate-cut Experimentssupporting
confidence: 87%
“…There are numerous articles dealing with the cryosectioning process or directly relevant to it Dubochet and McDowall, 1984;Dubochet et al, 1988;Hsieh et al, 2002;Jésior, 1986;Lickfeld, 1985;McDowall et al, 1983;Richter et al, 1991;Richter, 1994a,b,c;Sartori et al, 1993;Sartori Blanc et al, 1998;Sitte, 1996;Studer et al, 2001;Zhang et al, 2004;Zierold, 1984Zierold, , 1987) but many aspects remains uncertain or not understood. It is the aim of the present study to analyse in more detail the cutting artefacts and the cutting process and determine the optimal conditions for producing high quality vitreous sections.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous report on rat liver , we described the Wrst successful application of electron tomography to frozen-hydrated mammalian tissue. Artifacts associated with cryo-ultramicrotomy include knife marks, crevasses, chatter, and compression Chang et al, 1983;Frederik et al, 1982Frederik et al, , 1984Michel et al, 1991Michel et al, , 1992Richter et al, 1991;Richter, 1994;Zierold, 1994). Our tomographic analysis revealed that the Wrst two types of defects were predominantly conWned to the section surface, and that there was considerable useful ultrastructural information in the interior of the sections .…”
Section: Introductionmentioning
confidence: 81%
“…Al-though we have stated before that tomography is limited to 1-μm-thick objects, this can be circumvented using cryo-sectioning (after high-pressure freezing). This technique can provide thin sections of 70 nm thickness of any kind of a large bacterium or without chemical fixation [Richter et al, 1991]. An additional EM option is elemental analysis: the normally 'useless' inelastically scattered electrons in a standard electron microscope can be correlated to an element by energy-filtered imaging.…”
Section: Discussionmentioning
confidence: 99%